Analisis Kemampuan Penalaran dalam Menyelesaikan Masalah Trigonometri Ditinjau dari Gaya Berpikir Model Gregorc Siswa SMA - Lengga, Merlin Jeny; Samo, Damianus Dao; Blegur, Irna Karlina Sensiana (Circle: Jurnal Pendidikan Matematika, 2025)
This study aims to describe student’s mathematical reasoning abilities in solving trigonometry problems based on Gregorc thinking styles among XI students at SMA Negeri 1 Lobalain. The  research adopts a descriptive qualitative approach. Data collection techniques include thinking style questionnaires, test questions and interviews. The data analysis process follows the Miles and Huberman model, which consists of data reduction, data presentation and conclusion drawing. The results showed that, students with concrete sequential (SK) thinking style only fulfilled the indicators of presenting mathematical statements and using patterns and relationships to analyze mathematical situations. Students with abstract sequential (SA) thinking style are better at reasoning than students with other thinking style categories, but have not been able to fully compile and provide reasons for the correctness of the solution where abstract sequential thinkers are unable to provide reasons for the solution obtained from the problem. Students with a concrete random (AK) thinking style also did not fulfill all indicators of mathematical reasoning. They were only able to present mathematical statements and utilize patterns and relationships to analyze mathematical situations. Meanwhile, students with abstract random (AA) thinking style were only able to present mathematical statements.